Functional gold nanoparticles in diagnosis and treatment of cancer: A systematic review - Bingrui Li; Maihemuti Yakufu; Ru Xie; Hanfei Peng; Xiaohu Mi; Hairegu Tuxun (APL Materials)
Early diagnosis and prompt treatment of cancer are critical to reducing mortality rates and enhancing patient quality of life. Nanotechnology-driven cancer diagnosis and treatment are emerging approaches widely adopted in early cancer diagnosis and treatment, effectively addressing the high costs, potential radiation risks, and sensitivity limitations of traditional methods. Among the diverse range of nanomaterials, gold nanoparticles (Au NPs) have demonstrated remarkable potential for cancer diagnosis and treatment owing to their exceptional physicochemical stability and distinctive localized surface plasmon resonance effect. Moreover, their small size enables Au NPs to target malignant tumor tissues passively through the enhanced permeation and retention effect. This review begins with a concise overview of the optical properties of Au NPs, followed by an examination of the detection mechanism of Au NP-based biosensors for cancer markers and a systematic summary of the related early diagnosis studies. The latest advances in Au NPs-based optical therapeutic technology research, including photothermal therapy, photodynamic therapy, and combination therapy in the field of cancer treatment, are highlighted. Finally, this review provides an outlook for further applications of Au NPs in diagnostic and therapeutic integration.